CONTROL SYSTEM ENGINEERING DESIGN IN THREE PHASE MOTOR - Hendra Lesmana; Aqwam Rosadi Kardian, SKom, MM Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Komputer, 2000)
This study aimed to determine whether the computer can be used to control threephaseinduction motor with the help of Centronic interfaces and peripherals that runwith the program.These peripheral circuits consist of electronic components (circuit relay driver, relayand contactor magnet DC) which receives digital pulse from the interface thatoriginated from a computer and forward it to drive the relay pulse, peripheral circuitsare working with the help of a computer program that utilizes output data from thecard printer (LPT1) to communicate with peripherals that are made.